EKSPRESI LINGUISTIK TANAMAN JAGUNG SEBAGAI KEARIFAN LOKAL PENUTUR BAHASA TOMBULU - Imbang, Djeinnie; Kalangi, Leika M V.; Karamoy, Olga (Universitas Sam Ratulangi, 2020)
This research is focused on the anthropolinguistic study which is to observe the correlation between language and socio-cultural aspects based on the ethnicity of a certain linguistic community. This research aims to (a) identify and classify the linguistic forms regarding of maize in Tombulu language; and to (b) describe the forms of local wisdom pertaining maize.In this research, we used qualitative-descriptive method which is a form of problem-solving procedure that endeavors to describe the condition of research objects in the current times based on the observed empirical facts. The techniques and instruments for the data collection are through observation and in-depth interview. The interview is done in order to obtain the linguistic data that are in the form of verbal expressions and local wisdoms which are possessed by the farmer from Tombulu speaker. As for the data analysis, we used an anthropolinguistic analysis that focuses on the linguistic data without neglecting the local wisdoms that are inherent to the observed society. Thus, it is found that the linguistic form regarding to maize such as words, phrases, idioms, and local wisdoms are mapalus and cosmic knowledge relating to the crop.Keywords: linguistic expression, Tombulu language, local wisdom